تطبيقات النظرية التوليدية التحويلية في سورة الفاتحة أنموذجا = Applications of transformational generative grammar theory in Sūrah al-Fātiḥah - Mohamad Kamal, Nurul Afiqah; Yeob, Shamsul Jamili; Ali, Asem Shehadeh Saleh (Electronic Interdisciplinary Miscellaneous Journal (EIMJ), 2023)
Transformative Generative Theory (TGG) is one of the most important and prominent modern linguistic theories proposed and promoted by an eminent Western linguist, A. Noam Chomsky in1957. The theory contains distinct concepts which contributes immensely to linguistic studies. Inevitably, in dealing with this theory, there are two pertinent concepts which will assist a language user in understanding his language capability, and they are: deep structure and surface structure where the first one occurs in language user’s brain whereby the second structure is resemblance to the concepts of le parole as per prescribed by De Saussure of which it appears either in the oral form or written. Thus, the study envisages examining the relationship between Transformative Generative Theory and its concepts i.e. deep structure and surface structure. It also aims at identifying relationship between the theory of “generative” and the concept of “deep structure” as well as the theory of “transformative” and the concept of “surface structure”, where eventually it will unveil similarities and differences between them. The study adopts descriptive and analytical methodologies to explore the existence of the theory and the concepts in Sūrah al-Fātiḥah as well to reveal relationship between them (theory and concepts) in entire al-Qur’ān.